Paraventricular nucleus administration of DuP753 or PD123319 inhibits the effects of angiotensin on water and sodium intake - Do-Prado, M. H. [UNESP] (1996)
We determined the effects of DuP753 and PD123319 (both nonpeptides and selective antagonists of the AT1 and AT2 angiotensin receptors, respectively), and [Sar1, Ala8]ANG II (a non-selective peptide antagonist of angiotensin receptors) on water and 3% NaCl intake induced by administration of angiotensin II (ANG II) into the paraventricular nucleus (PVN) of sodium-depleted Holtzman rats weighing 250-300 g. Twenty hours before the experiments, the rats were depleted of sodium using furosemide (10 ng/rat, sc). The volume of drug solution injected was 0.5 μl over a period of 10-15 sec. Water and sodium intake were measured at 0.25, 0.5, 1.0 and 2.0 h. Pre-treatment with DuP753 (14 rats) at a dose of 60 ng completely abolished the water intake induced by injection of 12 ng of ANG II (15 rats) (6.4 ± 0.6 vs 1.4 ± 0.3 ml/2 h), whereas [Sar1, Ala8]ANG II (12 rats) and PD123319 (10 rats) at the doses of 60 ng partially blocked water intake (6.4 ± 0.6 vs 2.9 ± 0.5 and 2.7 ± 0.2 ml/2 h, respectively). In the same animals, [Sar1, Ala8]ANG II, DuP753, and PD123319 blocked the sodium intake induced by ANG II (9.2 ± 1.6 vs 3.3 ± 0.6, 1.8 ± 0.3, and 1.4 ± 0.2 ml/2 h, respectively). These results indicate that both DuP753 and PD123319, administered into the PVN, blocked the water and sodium intake induced by administration of ANG II into the same site.